The prostate monologues : what every man can learn from my humbling, confusing, and sometimes comical battle with prostate cancer - McCallum, Jack, 1949- (Rodale, 2013)
Draws on the author's own experiences with prostate cancer to address concerns many patients do not feel comfortable asking their doctors, drawing on the latest research to provide information in a reassuring format.